Characterization of Nonaflatoxigenic Aspergillus flavus/oryzae Strains Isolated from Korean Traditional Soybean Meju. Issue 6 (2nd November 2022) - Jun, Sang-Cheol; Kim, Yu-Kyung; Han, Kap-Hoon
Abstract: Filamentous fungi that could be classified into Aspergillus flavus / oryzae were isolated from traditionally fermented meju commercially available in Korea. The samples were analyzed for aflatoxin B1 and ochratoxin A contamination by HPLC; however, no toxin was detected. In addition, fungal and bacterial metagenomic sequencing were performed to analyze the microbial distribution in the samples. The results revealed that the distribution and abundance of fungi and bacteria differed considerably depending on the production regions and fermentation conditions of the meju samples. Through morphological analysis, ITS region sequencing, and assessment of the aflatoxin-producing ability, a total of 32  A. flavus/oryzae strains were identified. PCR analysis of six regions with a high mutation frequency in the aflatoxin gene cluster (AGC) revealed a total of six types of AGC breaking point patterns. The A. flavus/oryzae strains did not exhibit the high amylase activity detected in the commercial yellow koji strain (starter mold). However, their peptidase and lipase activities were generally higher than that of the koji isolates. We verified the safety of the traditionally fermented meju samples by analyzing the AGC breaking point pattern and the enzyme activities of A. flavus/oryzae strains isolated from the samples. The isolated strains could possibly be used as starter molds for soybean fermentation.